Brief Time-Based Activity Pacing Instruction as a Singular Behavioral Intervention was not Effective in Participants with Symptomatic Osteoarthritis - Murphy, Susan Lynn (Pain, 2016)
Osteoarthritis (OA) of the lower extremities is a prevalent cause of disability in which symptoms interfere with mobility and activity participation. Behavioral self-management for OA symptomatology is commonly recommended; but these interventions are underutilized, unstandardized in application, and at times, unavailable in the context of clinical care. For people with chronic pain, rehabilitation professionals may select to apply activity pacing instruction as one behavioral strategy to manage symptoms. Activity pacing is widely used in combination with other pharmacological and behavioral interventions but has not been studied as a singular behavioral intervention for people with OA. The purpose of this study was to evaluate the effectiveness of an occupational therapist-delivered, time-based activity pacing program for treatment of pain, fatigue, and physical function in people with symptomatic knee or hip OA. A 3-arm randomized controlled trial was conducted in which 193 people were randomized into tailored activity pacing, general activity pacing, or usual care arms. Assessments were done at 10 weeks and 6 months post baseline. Using linear mixed models, WOMAC pain scores changed over time, decreasing the most in the general and usual care groups; only the usual care group had decreased pain over 6 months. The tailored and general activity pacing groups reported higher frequency of pacing behaviors than the usual care group at 10 weeks but pacing was not sustained at 6 months. This trial does not support the use of time-based pacing as a singular behavioral strategy for people with knee or hip OA.